Determinants of Brand Love in E-Commerce Platforms: The Role of Pop-Up Advertising, Satisfaction, Brand Awareness and Brand Association among Blibli Users in Jayapura City - Yohanis Rante; Indra Eka Wardana Toii (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to examine the determinants of brand love in e-commerce platforms by analyzing the influence of pop-up advertising, satisfaction, brand awareness, and brand association on brand love among Blibli e-commerce application users. This research emphasizes understanding which factors contribute significantly to strengthening consumers’ emotional attachment and affection toward the brand. This study was conducted in Jayapura City, Papua, Indonesia, focusing on users of the Blibli e-commerce application. This research applied a quantitative approach. Data were collected through structured questionnaires distributed to active Blibli users in Jayapura City. Respondents were selected using purposive sampling, with criteria including individuals who have used the Blibli application and have conducted transactions through the platform. Data analysis was performed using Structural Equation Modeling (SEM) with SmartPLS 4.0 to evaluate the proposed hypotheses and test the relationships among the variables. The findings reveal that brand awareness and brand association have a positive and significant effect on brand love among Blibli users in Jayapura City. However, pop-up advertising and satisfaction do not show a positive and significant influence on brand love, indicating that intrusive promotional formats and transactional satisfaction alone are insufficient to generate deep emotional attachment. The results suggest that consumer’s emotional connection to the brand is more strongly shaped by brand perception and brand meaning rather than advertising exposure and short-term satisfaction. This study concludes that brand love in e-commerce platforms is significantly driven by consumer’s cognitive perception of the brand, particularly through brand awareness and brand association. In contrast, pop-up advertising and satisfaction are not proven to strengthen brand love. Therefore, Blibli should prioritize strategies that enhance brand identity, strengthen brand image, and create distinctive associations in consumer’s minds. This study contributes to branding literature and provides practical implications for e-commerce marketing strategies.